Inhibition, Executive Function, and Freezing of Gait - Cohen, Rajal G. (2014)
BACKGROUND: Studies suggest that freezing of gait (FoG) in people with Parkinson’s disease (PD) is associated with declines in executive function (EF). However, EF is multi-faceted, including three dissociable components: inhibiting prepotent responses, switching between task sets, and updating working memory. OBJECTIVE: This study investigated which aspect of EF is most strongly associated with FoG in PD. METHOD: Three groups were studied: adults with PD (with and without FoG) and age-matched, healthy adults. All participants completed a battery of cognitive tasks previously shown to discriminate among the three EF components. Participants also completed a turning-in-place task that was scored for FoG by neurologists blind to subjects’ self-reported FoG. RESULTS: Compared to both other groups, participants with FoG showed significant performance deficits in tasks associated with inhibitory control, even after accounting for differences in disease severity, but no significant deficits in task-switching or updating working memory. Surprisingly, the strongest effect was an intermittent tendency of participants with FoG to hesitate, and thus miss the response window, on go trials in the Go-Nogo task. The FoG group also made slower responses in the conflict condition of the Stroop task. Physician-rated FoG scores were correlated both with failures to respond on go trials and with failures to inhibit responses on nogo trials in the Go-Nogo task. CONCLUSION: These results suggest that FoG is associated with a specific inability to appropriately engage and release inhibition, rather than with a general executive deficit.